2012
DOI: 10.1136/bmjopen-2012-001392
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey and service evaluation of simple telehealth in primary care: what do patients think?

Abstract: ObjectiveTo determine the patient experience of using a simple telehealth strategy to manage hypertension in adults.DesignAs part of a pragmatic service evaluation, the acceptability of, satisfaction with and ease of use of a simple telehealth strategy was determined via text, cross-sectional questionnaire survey administered by telephone, case studies, discussion groups and informal feedback from practices. This simple telehealth approach required patients to take home blood pressure (BP) readings and text th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 12 publications
(9 reference statements)
2
48
0
Order By: Relevance
“…A feasibility study done in lowrisk pregnant women showed a preference for blood pressure selfmonitoring with a reduced schedule of antenatal visits, and no change in anxiety levels [22]. Literature on blood pressure self-monitoring outside pregnancy indicates patients are confident at self-monitoring and report high levels of satisfaction and feelings of involvement, control, and support for their health [23,24]. In the current study similar findings for self-testing of urine are reported; women whose readings were used by HCPs felt valued and involved in their own care and reported positive experiences.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…A feasibility study done in lowrisk pregnant women showed a preference for blood pressure selfmonitoring with a reduced schedule of antenatal visits, and no change in anxiety levels [22]. Literature on blood pressure self-monitoring outside pregnancy indicates patients are confident at self-monitoring and report high levels of satisfaction and feelings of involvement, control, and support for their health [23,24]. In the current study similar findings for self-testing of urine are reported; women whose readings were used by HCPs felt valued and involved in their own care and reported positive experiences.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…Recent manuscripts further demonstrate the feasibility of virtual environments for educating adults with chronic illness. 62,63,64 Additionally, studies of telehealth programs show at least short-term clinical improvements for BP outcomes; such findings may be explained in part because home BP readings may be more reliable than those obtained in a physician's office because of ''white coat syndrome'' in which a patient's BP is elevated in the clinical setting, but not in other settings. As more robust studies emerge, it will be helpful to have a systematic review and/or meta-analysis conducted to show positive and negative impact of BP studies by type of intervention.…”
Section: Discussionmentioning
confidence: 94%
“…To address the need for information about telemonitoring implementation in clinical practice, we focus here on the experiences of the nurses, physicians, and patients who submitted, received, and reviewed these home BG and BP data. Previous examinations of primary care telemonitoring implementations have been limited to examinations of feasibility and acceptability, [15][16][17] a single stakeholder perspective, 15,18,19 or centralized monitoring by research personnel not well integrated with the primary practice site. [20][21][22] The clinical trial that is the background for this work was very much an effectiveness trial.…”
Section: Introductionmentioning
confidence: 99%